The Role of Maori Women in Treaty Negotiations and Settlements - Rangiheuea, Tania (Victoria University of Wellington Law Review, 1995)
The author addresses some key issues confronting Māori women in respect of Treaty settlements and offers suggestions on why a repudiation of the existing arrangements between Māori and the Crown are essential. In the broader context, the author argues that the Government has been on a campaign to privatise public and community assets and deregulating markets, aggravating societal inequality. Māori women particularly suffer from their socioeconomic status as Māori. Furthermore, the author criticises the lack of a system to guarantee a place for Māori women within their own institutions or organisations in respect of asset management and decision-making. The author concludes that it is essential to share the benefits of real change with Māori women who are the least empowered. To do this, a settlement framework centred around people and life (rather than a purely money-driven model) is needed.